2014
DOI: 10.3329/cmoshmcj.v13i3.21021
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Infertility Among Couples Seeking Treatment in A Selected Clinic in Dhaka City

Abstract: Background: Infertility is a global health issue affecting approximately 8-10% of couples and has multidimensional problem with social, economic and cultural implications, which can take threatening proportions in countries with strong demographic problems. Objective: To investigate the determinants of infertility among couples seeking treatment. Methodology: A cross sectional study was conducted in selected private clinic of Dhaka city among 196 infertile couple by face to face interview using pretested semi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
5
7
0
Order By: Relevance
“…The final model of the study's logistic regression analysis indicates that the risk of infertility in Turkey is associated with the age of women, educational levels of couples, age at first marriage, age at first menstruation and the BMI of women. The age of women as a risk factor for infertility is well-documented, with the risk of infertility increasing as a woman's age increases (Van Noord-Zaadstra et al, 1991;Gougeon, 2005;Swanton & Child, 2005;Romero et al, 2008;Terävä et al, 2008;Adamson et al, 2011;Dhont et al, 2011;Bushnik et al, 2012;Chowdhury et al, 2014;Direkvand-Moghadam et al, 2015), and a similar result was found in the present study. The risk of infertility among women aged 35-39 was found to be higher by 30% compared with women aged 15-25.…”
Section: Discussionsupporting
confidence: 87%
“…The final model of the study's logistic regression analysis indicates that the risk of infertility in Turkey is associated with the age of women, educational levels of couples, age at first marriage, age at first menstruation and the BMI of women. The age of women as a risk factor for infertility is well-documented, with the risk of infertility increasing as a woman's age increases (Van Noord-Zaadstra et al, 1991;Gougeon, 2005;Swanton & Child, 2005;Romero et al, 2008;Terävä et al, 2008;Adamson et al, 2011;Dhont et al, 2011;Bushnik et al, 2012;Chowdhury et al, 2014;Direkvand-Moghadam et al, 2015), and a similar result was found in the present study. The risk of infertility among women aged 35-39 was found to be higher by 30% compared with women aged 15-25.…”
Section: Discussionsupporting
confidence: 87%
“…In our study bilateral tubal block was in 7% of the infertile women where as in a study in Nigeria tubal occlusion was in 16.9% 14 and bilateral tubal blockage in 15.6% and 28.9% of the infertile women 15,3 which are quite high than our series. Anovulation was in 17% in our study and 22.3% 16 in other study.…”
Section: Discussionsupporting
confidence: 56%
“…According to the findings of different studies, reproductive system disorders like sexually transmitted disease and endometrial and ovarian dysfunction, genetic factor, age, alcohol consumption, smoking, obesity, irregular menstrual cycle, age at menarche, age at marriage, and dysmenorrhea are found to be factors affecting infertility [3,10,11].…”
Section: Introductionmentioning
confidence: 99%